Efficacy of Trichoderma harzianum and Pseudomonas fluorescens against wilt of cumin (Cuminum cyminum L.) (Indian Journal of Arid Horticulture, 2017)
Efficacy of bioagents like T. harzianum and P. fluorescens alone or with combined inoculation as seed treatment andsoil application along with or without vermicompost were evaluated against wilt of cumin caused by Fusarium oxysporum f.sp. cumini under field conditions Rabi 2013-14 and 2014-15. Among all the treatments, combined inoculation of T.harzianum + P. fluorescens as seed treatment (4+4 gm/kg seed) and soil application (2.5+2.5 kg/ha.) along withvermicompost resulted minimum disease incidence (15.82%) and highest per cent disease control (64.42%) followed by T.harzianum + P. fluorescens combined application as seed treatment (4+4 gm/kg seed) and soil application (2.5+2.5 kg/ha.)without vermicompost. These treatments were also found effective on the dry weight of cumin plants. The shoot, root lengthsand cumin seed yield were significantly increased in response to bioagent treatments. Highest shoot, root lengths and seedyield were also recorded in combined inoculation of bioagent treatments i.e. T. harzianum + P. fluorescens as seed treatment(4+4 gm/kg seed) and soil application along with vermicompost (2.5+2.5 kg/ha.) closely followed by T. harzianum + P.fluorescens seed treatment (4+4 gm/kg seed) and soil application (2.5+2.5 kg/ha.) without vermicompost. Whereas, rest ofthe treatments were found least effective on shoot, root lengths and seed yield of the cumin.
Keywords: Cumin; wilt; Fusarium oxysporum f. sp. cumini; T. harzianum; P. fluorescens